2015
DOI: 10.1111/jvim.12512
|View full text |Cite
|
Sign up to set email alerts
|

Complication Rates Associated with Transvenous Pacemaker Implantation in Dogs with High‐Grade Atrioventricular Block Performed During versus After Normal Business Hours

Abstract: BackgroundTransvenous pacemaker implantation in dogs is associated with a relatively high complication rate. At our institution, pacemaker implantation in dogs with high‐grade atrioventricular block (HG‐AVB) frequently is performed as an after‐hours emergency.HypothesisAmong dogs with HG‐AVB, the rate of major complications is higher when pacemakers are implanted after hours (AH) compared to during business hours (BH).AnimalsClient‐owned dogs with HG‐AVB that underwent transvenous pacemaker implantation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 20 publications
4
36
0
Order By: Relevance
“…As a consequence of the historically poor prognosis associated with PAS, it has been suggested that dogs with this disease are less ideal candidates for PM implantation than those affected by other bradyarrhythmias [89]. However, when considering reported data about survival times after PM implantation for other bradyarrhythmias, it appears that dogs with PAS have similar survival times [2,7,71,74,75,124,125].…”
Section: Indications For Pacing and Choice Of Pacing Modementioning
confidence: 99%
“…As a consequence of the historically poor prognosis associated with PAS, it has been suggested that dogs with this disease are less ideal candidates for PM implantation than those affected by other bradyarrhythmias [89]. However, when considering reported data about survival times after PM implantation for other bradyarrhythmias, it appears that dogs with PAS have similar survival times [2,7,71,74,75,124,125].…”
Section: Indications For Pacing and Choice Of Pacing Modementioning
confidence: 99%
“…The generator site is the most common site of infection reported in dogs and people, with lead infections occurring less frequently. 1,3,5,6 In situations where the pacemaker generator site was associated with infection in dogs, in all cases it was grossly inflamed and abnormal. 6 Pre-existing myocarditis cannot be completely excluded in this case, as AV block is a recognised ECG abnormality in dogs with myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…abscess or otitis externa). 1,3,5,6 Placement of the pacemaker generator over the thoracic region rather than the cervical region may have also accounted for reduced infection rates in one canine study. 5 Prior placement of a temporary pacemaker lead and duration of procedure were not found to be associated with increased risk of infection in dogs, in contrast to findings for humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations